Rat B2 Sequences Are Induced in the Hippocampal CA1 Region After Transient Global Cerebral Ischemia - Liu, Xiaodong; Clemens, James A.; Yin, Tinggui; Stephenson, Diane T.; Johnstone, Edward M.; Du, Yansheng; Panetta, Jill A.; Paul, Steven M.; Little, Sheila P. (The Journal of biological chemistry, 1999)
Global brain ischemia causes cell death in the CA1 region of the hippocampus 3–5 days after reperfusion. The biological pathway leading to such delayed neuronal damage has not been established. By using differential display analysis, we examined expression levels of poly(A) RNAs isolated from hippocampal extracts prepared from rats exposed to global ischemia and found an up-regulated transcript, clone 17a. Northern blot analysis of clone 17a showed an approximately 35-fold increase in the ischemic brain at 24 h after four-vessel occlusion. Rapid amplification of cDNA ends of clone 17a revealed a family of genes (160–540 base pairs) that had the characteristics of rodent B2 sequences. In situ hybridization demonstrated that the elevated expression of this gene was localized predominantly in the CA1 pyramidal neurons. The level of expression in the CA1 region decreased dramatically between 24 and 72 h after ischemia. The elevated expression of clone 17a was not observed in four-vessel occlusion rats treated with the compound LY231617, an antioxidant known to exert neuroprotection in rats subjected to global ischemia. Since delayed neuronal death has the characteristics of apoptosis, we speculate that clone 17a may be involved in apoptosis. We examined the expression level of clone 17a inin vitro models of apoptosis using cerebellar granule neurons that were subjected to potassium removal, glutamate toxicity, or 6-hydroxydopamine treatment and found that clone 17a transcripts were induced in cerebellar granule neurons by glutamate or 6-hydroxydopamine stimulation but not potassium withdrawal.